(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
On September 14, 2023, an expert research group made up of a team of NASA scientists released their final report on "unidentified aeronautical phenomena (UAPs)," which include unidentified flying objects (UFOs) and natural phenomena. General impressions regarding this report are stated.